Distributed Voronoi coverage algorithm in wireless sensor networks - XU Peng-fei1; CHEN Zhi-gang1; DENG Xiao-heng1 (Tongxin xuebao)
On the hypothesis conditions that wireless sensor networks only covered partial target region and the commu-nication radius was no less than twice of the sensing radius,a coverage-preserved and connected distributed Voronoi cov-erage algorithm was presented.Firstly,a method of detecting coverage redundancy sensors based on the local Voronoi re-gions was proposed,whose computational complexity was unconcerned with the density of sensors.Then,an en-ergy-prior self-scheduling strategy based on local Voronoi neighbors was proposed,where those sensors that were com-munication neighbors but not local Voronoi neighbors could synchronously execute self-scheduling,which improved the astringency of distributed scheduling.The simulation results show that the average number and coverage-degree of active sensors produced by the proposed algorithm are close to the centralized algorithm and smaller than the general distributed algorithm,while the proposed algorithm has more advantages in terms of active sensors’ average energy,scheduling as-tringency and runtime.